Peripheral nerve entrapments-rare causes of a common condition: case series - Laura Mendes de Barros; Adilson Jose Manuel de Oliveira; Alan de Souza Santos; Flávio Leão Lima; Rodolfo Silva Valente (University of São Paulo, 2021)
Compressive syndromes of peripheral nerves both in the upper and lower limbs are part of daily clinical practice; however, the etiological diagnosis can be challenging and impact on the outcome of the patient. We report five cases with rare etiologies of nerve entrapments: one in the lower limb and four in the upper limbs with the final diagnosis made only during the operation. The patients evolved without post-operative complications and had good outcomes. This series includes the first report of sciatic compression by a lipoma in the popliteal fossa, two lipomas one with compression of infraclavicular brachial plexus and another with compressing the posterior interosseous nerve, and two reports of vascular lesions due to blunt traumas, which are also uncommon. This series adds to the literature more hypotheses of differential diagnoses in nerve entrapments, which is fundamental to surgical decisions and pre-operative planning-and perhaps most importantly prevents wrong diagnosis of idiopathic compressions, which would lead to a completely wrong approach and unfavorable outcomes.